Teknik Pengukuran Untuk Benda Beraturan dan Tidak Beraturan: Tantangan dan Solusi - Pratama, Sulton Galih; Harnani, Lintang Kurnia; Ramadhani, Charisma; Ningsih, Nunung Rahayu; Safitri, Riya; Sudarti, Sudarti; Baihaqi, Habibah Khusna (Innovative: Journal Of Social Science Research, 2025)
Physics is a science that studies objects, their motion, and their benefits to human life. Measurement in physics is the activity of comparing the measured quantity with another quantity that has been established as a unit. Regular objects, such as spheres, blocks, and cubes, have shapes that can easily be calculated using geometric formulas. In contrast, irregular objects pose a greater challenge because their shapes cannot be simply represented by geometric equations. This study aims to identify the measurement techniques used for both regular and irregular objects in terms of accuracy and efficiency. The methods discussed include techniques for determining the volume and density of objects. This experiment provides better insights into the selection of appropriate measurement methods based on the characteristics of the object being measured. The results of the experiment show that measuring regular objects is easier with simple measuring tools, while irregular objects require more careful and precise approaches to obtain accurate results. Measurement errors can occur, especially when measuring irregular objects, which can be minimized by using proper measuring tools and following correct procedures.